(untitled) - Nguyen Minh Hoat (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The Ede epic is a part of the epic of the Central Highlands, Vietnam, created by the Ede people in the early period of history. This is a genre filled with fictional, beautiful colors; its language has rhymes, rhythms, describing heroic feats in labor and combat; monumental and majestic images of major events taken place in the life of the community. The epic of Ede comprehensively reflects the economic, social life and customs of Ede people. It, simultaneously, expresses a desire of the nation on a happy and prosperous life; praises love, nobility, and human courage before the trials of nature and in the struggle against evil. The paper examines the art of rhetorical comparison in the Ede epic of the Central Highlands in Vietnam on the aspects of comparative structure, comparative factors and the value of the art of rhetorical comparison in the Ede epic. Thereby, it also clarifies the cultural characteristics of the Ede people in ancient times.